2021
DOI: 10.3390/brainsci11040476
|View full text |Cite
|
Sign up to set email alerts
|

Post-Training Sleep Modulates Topographical Relearning-Dependent Resting State Activity

Abstract: Continuation of experience-dependent neural activity during offline sleep and wakefulness episodes is a critical component of memory consolidation. Using functional magnetic resonance imaging (fMRI), offline consolidation effects have been evidenced probing behavioural and neurophysiological changes during memory retrieval, i.e., in the context of task practice. Resting state fMRI (rsfMRI) further allows investigating the offline evolution of recently learned information without the confounds of online task-re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
(116 reference statements)
0
13
0
Order By: Relevance
“…For instance, enhanced functional connectivity is reported within the ventral default mode network, as well as between two subsystems of the default mode network, which correlates with behavioral performance after TSD ( Chen et al, 2018 ). Functional connectivity between navigation-related brain structures increases during relearning in the extended environment after TSD, which represents the use of compensatory brain resources ( Deantoni et al, 2021 ). The increased functional connectivity between the thalamus and precuneus under TSD conditions is paralleled with greater recovery of working memory performance ( Yoo et al, 2007 ; Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, enhanced functional connectivity is reported within the ventral default mode network, as well as between two subsystems of the default mode network, which correlates with behavioral performance after TSD ( Chen et al, 2018 ). Functional connectivity between navigation-related brain structures increases during relearning in the extended environment after TSD, which represents the use of compensatory brain resources ( Deantoni et al, 2021 ). The increased functional connectivity between the thalamus and precuneus under TSD conditions is paralleled with greater recovery of working memory performance ( Yoo et al, 2007 ; Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The navigation task is described in detail elsewhere (Deantoni et al, 2021), only essential information is reported here. Participants were trained in a previously used virtual navigation environment (Orban et al, 2006; Peigneux et al, 2006; Rauchs, Orban, Balteau, et al, 2008), that features a complex town made of two levels communicating through two teleports (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the four 8-minute blocks of free exploration, participants are exposed to 10 test trials in a row to estimate their navigation performance. A quantitative performance measure is computed for each trial as the shortest distance remaining between the subject’s actual location at the end of the trial time limit and the location of the target destination, based on video screen recordings of their navigation (Deantoni et al, 2021; Orban et al, 2006; Peigneux et al, 2006; Rauchs, Orban, Balteau, et al, 2008). Participants were also tested on 10 L1 navigation trials during a fMRI session on Day 1 after learning before DWI-2 and on Day 4 before relearning after DWI-3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occurrence and strength, especially of hippocampal replay patterns, were correlated with subsequent memory performance 15,16 . Similarly, two human 3T-fMRI studies investigated whether FC-modulation in the resting-state was associated with a previous declarative learning task 17,18 . Although these studies detected a few modulated connections in predefined regions activated during encoding, these were not correlated with memory performance and not controlled for the natural variation of the participant’s resting-state between consecutive measurements.…”
Section: Introductionmentioning
confidence: 99%